The economics of political borders - Enrico Spolaore (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper presents concepts from economic analysis that shed light on the formation and breakup of sovereign states. First, we discuss the key trade-off between economies of scale in the provision of public goods and political costs from heterogeneity of preferences. Second, we present four economic perspectives on the formation of borders: efficient borders, borders as democratic outcomes, borders in a world of rent-seeking Leviathans, and borders as outcomes of conflict and wars. Finally, we provide an analytical illustration of the basic ideas within a simple framework.
Keywords: N41; 330; economies of scale; heterogeneity costs; conflict; size of nations; Grenze; Landesgröße; Politischer Konflikt; Skalenertrag; Public Choice; Theorie